Uso do MapCHECK 2 para controle de qualidade em planejamento computadorizado de IMRT - Pelicano, Pedro Siqueira [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The objective of this study is to analyze the effectiveness of the use of the MapCHECK®2 dosimetry equipment, manufactured by Sun Nuclear Corporation, in the routine procedures for quality control of individual radiotherapy patient schedules. The equipment consists of a flat array with 1.527 diodes detectors arranged in a grid of 32.0cm x 26.0cm. The diodes are uniformly distributed across the matrix, with a spacing of 7.07 mm. The radiation dose distribution in the treatment plane is evaluated on a map of the radiation beam fluence in the irradiated tissue. For IMRT (Modulated Beam Radiotherapy), the equipment is able to detect misalignments in the movement of the leaf collimator of more or less 1mm and its resolution of 0.8x0.8mm is ideal for analyzing regions of high dose gradient. For MapCHECK 2 calibration a clinical linear accelerator (clinac) Varian Medical Systems was used with photon beams of E1 = 10.0 MV and E2 = 6.0 MV. The device was positioned at a distance DFD = 100.0cm. The radiation dose calculation was determined for the depths dA = 5.0cm and dB = 10.0cm. To ensure backscattering, 10 plates of solid water were used, representing a thickness of 10.0 cm, placed below the MapCHECK 2 and on the treatment table. Fifteen radiotherapy plans were evaluated using the IMRT technique. For exposure of the device and verification of the linearity of the detector response, 100 UM and 200 UM (monitor units) were applied. The calculated value of the radiation dose in depth was compared with the value measured with MapCHECK2, 80% of the analyzed schedules presented differences below 1.0%. The greatest variation was 1.92% and it was given to the energy of 6 MV in the depth d = 5.0cm in only one of the evaluated cases. For the clinical cases analyzed, MapCHECK 2 proved to be efficient for the evaluation of the radiation dose distribution in radiotherapy plans

O objetivo deste estudo é analisar a eficácia do uso do equipameto de dosimetria MapCHECK®2, fabricado pela Sun Nuclear Corporation, nos procedimentos de rotina para controle de qualidade de planejamentos radioterápicos individuais de pacientes. O equipamento constitui de uma matriz plana com 1527 diodos detectores dispostos em uma grade de 32,0cm x 26,0cm. A separação entre os detectores é de 7,07 mm por toda a matriz, de maneira uniforme. A distribuição de dose de radiação no plano de tratamento é avaliada em uma mapa de fluência do feixe de radiação no tecido irradiado. Para tratamentos com a técnica de IMRT (radioterapia por intensidade modulada do feixe), o equipamento é capaz de detectar desalinhamentos no movimento das lâminas do colimador de mais ou menos 1mm e sua resolução de 0,8x0,8 mm é ideal para analisar regiões de gradiente de alta dose. Para calibração do MapCHECK 2 utilizou-se um acelerador linear clínico (clinac) da marca Elekta Medical Systems, modelo Precise, com feixes de fótons de energias de E1 = 10,0 MV e E2 = 6,0 MV. O dispositivo foi posicionado à uma distância DFD = 100,0cm. O cálculo de dose de radiação foi determinado para as profundidades dA = 5,0cm e dB = 10,0cm. Para se garantir o retroespalhamento foi utilizado 10 placas de água sólida, representando uma espessura de 10,0cm, colocadas abaixo do MapCHECK 2 e sobre a mesa de tratamento. Foram avaliados 15 planejamentos radioterápicos com a técnica de IMRT. Para exposição do dispositivo e verificação da linearidade da resposta dos detectores, foram aplicadas 100 UM e 200 UM (unidades monitoras). O valor calculado da dose de radiação na profundiade foi comparado com o valor medido com o MapCHECK 2, 80% dos planejamento analisados apresentaram diferênças inferiores à 1,0%. A maior variação foi de 1,92% e se deu para a energia de 6 MV na profunidade d = 5,0cm em apenas um dos casos avaliados. Para os casos clínicos analisados, o MapCHECK 2 mostrou-se eficiente para avaliação da distribuição de dose de radiação em planejamentos radioterápicos
Keywords: Linear accelerator; Quality control; Radiation dose; Radiotherapy by beam modulated intensity (IMRT); Controle de qualidade; Dose de radiação; MapCHECK®2; Radioterapia por intensidade modulada de feixe (IMRT); Acelerador linear